2012
DOI: 10.1186/1471-2393-12-163
|View full text |Cite
|
Sign up to set email alerts
|

Contradictions and conflict: A meta-ethnographic study of migrant women’s experiences of breastfeeding in a new country

Abstract: BackgroundStudies report mixed findings about rates of both exclusive and partial breastfeeding amongst women who are migrants or refugees in high income countries. It is important to understand the beliefs and experiences that impact on migrant and refugee women’s infant feeding decisions in order to appropriately support women to breastfeed in a new country. The aim of this paper is to report the findings of a meta-ethnographic study that explored migrant and refugee women’s experiences and practices related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
66
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 54 publications
9
66
0
Order By: Relevance
“…Nevertheless, there were three relevant literature reviews from Australia, one on postnatal depression and cultural perspectives, 27 one on the importance of cultural safety for Australian midwifery practice 6 and a meta-ethnographic study of migrant women's experiences of breastfeeding in Australia. 34 …”
Section: Literature Search Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, there were three relevant literature reviews from Australia, one on postnatal depression and cultural perspectives, 27 one on the importance of cultural safety for Australian midwifery practice 6 and a meta-ethnographic study of migrant women's experiences of breastfeeding in Australia. 34 …”
Section: Literature Search Resultsmentioning
confidence: 97%
“…A UK study 27 examined the effect of caseload midwifery practices on a culturally diverse group and one Australian study 4 compared the obstetric intervention rates and birth outcomes between Australian and overseas born. Also included in the review were ten literature reviews 6,7,[27][28][29][30][31][32][33][34] (Table 3), one book chapter, 22 and three scholarly, but non-research articles; a clinical paper on the Migrant Health Guide in UK, 35 a report from the Lancet 36 and To explore the links between multiple deprivations and use of maternal services 21 Singh an opinion piece in Australian Midwifery News by an Indian midwife. 37 No research article was found specifically exploring Indian women's childbearing experiences in Australia.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Breast-feeding in public is one of the obstacles noted in the present and other studies conducted in Mexico (9,48,49) , in the Hispanic population in the USA (50) , in migrant populations (40) and in other populations (51) . In the present study it was ranked as the third main obstacle to breastfeed (D Bueno-Gutierrez and C Chantry, unpublished results).…”
Section: Breast-feeding In Publicmentioning
confidence: 91%
“…In southern and rural areas, where traditional practices are the norm, there are higher breast-feeding rates than in the northern, more urban, modern environments. There are other studies indicating that breast-feeding rates are decreasing in women migrating from traditional, rural areas to modern, urban societies with higher income (40)(41)(42) . Modernization implies acculturation or adoption of the values, beliefs and behaviours of the mainstream society (43) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation